García-Álvarez, Jacobo y Puente-Lozano, Paloma (eds.) (2022). Beneath the Lines: Borders and Boundary-Making from the 18th to the 20th Century - Raya Collado, Ana (Documents d’Anàlisi Geogràfica, 2023)
García-Álvarez, Jacobo y Puente-Lozano, Paloma (eds.) (2022) Beneath the Lines: Borders and Boundary-Making from the 18th to the 20th Century Madrid: Springer, 172 p. ISBN 978-3-030-96903-5